1997
DOI: 10.1111/j.1541-0072.1997.tb00012.x
|View full text |Cite
|
Sign up to set email alerts
|

Access to Health Care Among Three Cohorts of Older Americans Residing in a Rural State

Abstract: Three cohorts of older Americans are examined to determine how they perceive the likelihood of being able to access health care in the future. A modified Andersen (1968) model provides the framework for the study. A representative sample of 2,404 noninstitutionalized midwestern older persons separated into three age cohorts (60-69, 70-79, and 80+ ) was used. Predisposing, enabling, and need factors were examined by logistic regression. Significant differences were found between age cohorts, with the perceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
(37 reference statements)
1
9
0
Order By: Relevance
“…Finally, the need component of the model includes perceived or evaluated needs of the individual's physical and behavioral health status. In studies using the Andersen model, need-based factors often represent the most immediate determinants of service utilization and have been shown to explain the largest share of variance in utilization (Aday & Andersen, 1974;Andersen & Newman, 1973;Mercier & Shelley, 1997;Padgett et al, 1990).…”
Section: Conceptual Framework Of Service Utilizationmentioning
confidence: 98%
See 1 more Smart Citation
“…Finally, the need component of the model includes perceived or evaluated needs of the individual's physical and behavioral health status. In studies using the Andersen model, need-based factors often represent the most immediate determinants of service utilization and have been shown to explain the largest share of variance in utilization (Aday & Andersen, 1974;Andersen & Newman, 1973;Mercier & Shelley, 1997;Padgett et al, 1990).…”
Section: Conceptual Framework Of Service Utilizationmentioning
confidence: 98%
“…Although the model was initially applied to study the use of health care services, it has been extended to other service types for various populations (Bass & Noelker, 1987;Calsyn & Roades, 1993;Freedman, 1993;Mercier & Shelley 1997;McCaslin, 1989;Miller & McFall, 1991;Padgett, Patrick, Burns, & Schlesinger, 1994).…”
Section: Conceptual Framework Of Service Utilizationmentioning
confidence: 99%
“…Likewise, research has shown that the factors influencing access to medical care vary by age in later life. For example, higher co-pay and lack of insurance coverage are often attributed to lower self-reported accessibility to healthcare among the youngest-old adults (aged 60–69); whereas greater needs due to poor health and lack of transportation are more often attributed to lower accessibility of care among the oldest-old adults (aged 80 or older) [35].…”
Section: Introductionmentioning
confidence: 99%
“…Older Americans often wrestle with poor health. A sample of 2,404 noninstitutionalized Midwestern older persons in three age cohorts (Mercier & Shelley, 1997) found that rural elderly have higher rates of chronic illness and generally poorer health. Heard-Mueller, Darville, and Watson (1 994) discovered different patterns in health care utilization between black and white elderly rural women in Texas.…”
Section: Symposium On Rural Environment: Desoto/tajaeli/hofermentioning
confidence: 99%